Complex-phase fluorescent ceramic, preparation method thereof and light-emitting device
By using phosphor powder and alumina grains of multiple particle sizes in complex phase fluorescent ceramics and carrying out special sintering treatment, the contradiction between phosphor content and density is solved, and high phosphor content and high density is achieved Complex fluorescent ceramics improve their luminous performance and mechanical strength.
Patent Information
- Application Number
- CN202310748229.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-31
AI Technical Summary
In order to ensure density in complex phase fluorescent ceramics, the content of phosphor should not exceed 50%. High phosphor content can improve luminous performance, but it is difficult to take into account both high phosphor content and density.
By using at least two phosphor grains of different particle sizes and alumina grains in complex phase fluorescent ceramics, and coating SiO2 and Al2O3 layers on the surface of the phosphor particles, combining discharge plasma sintering and thermal isostatic sintering technology, Improve the binding force between phosphor and alumina grains and increase the content of phosphor grains to 70%-90%.
Complex-phase fluorescent ceramics with high phosphor content and high density are achieved, which improves its luminous performance and mechanical strength, while maintaining the original state of the luminous powder particles, avoiding the decline in luminous performance.
Smart Images

Figure CN119219408A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid-state lighting technology, and in particular to a complex phase fluorescent ceramic and a preparation method and a light-emitting device thereof. Background Art
[0002] At present, the fluorescent ceramics used in laser lighting display technology mainly include pure phase fluorescent ceramics and complex phase fluorescent ceramics. Among them, complex phase fluorescent ceramics are more popular due to their higher luminescence performance and thermal conductivity.
[0003] However, in the current complex phase fluorescent ceramics, in order to ensure the density of the fluorescent ceramics, the content of the fluorescent powder does not exceed 50%. In complex phase fluorescent ceramics, more fluorescent powder is needed to provide luminescent centers, thereby improving the luminescent performance of complex phase fluorescent ceramics.
[0004] The current contradiction in the preparation of fluorescent ceramics is to reduce the phosphor content to ensure the density of the fluorescent ceramics, and to increase the phosphor content to improve the luminescence performance of the fluorescent ceramics. Therefore, a complex fluorescent ceramic with high phosphor content and high density is urgently needed. Summary of the invention
[0005] The present application provides a complex phase fluorescent ceramic and a preparation method thereof, so as to obtain a complex phase fluorescent ceramic with high phosphor content and high density.
[0006] The present application first provides a complex fluorescent ceramic, which includes fluorescent powder grains and aluminum oxide grains; wherein the fluorescent powder grains include at least two fluorescent powder grains with different particle sizes; the aluminum oxide grains include at least two aluminum oxide grains with different particle sizes, wherein at least some of the small-size aluminum oxide grains are distributed around the fluorescent powder grains and connected to the fluorescent powder grains; the mass of the fluorescent powder grains is 70%-90% of the mass of the complex fluorescent ceramic.
[0007] The particle sizes of the two phosphor crystal particles with different particle sizes are respectively in the range of 10-30 μm and 3-10 μm.
[0008] The number of the phosphor crystal particles with small particle sizes accounts for 10-30% of the number of the phosphor crystal particles with large particle sizes.
[0009] The particle size ranges of the two aluminum oxide grains with different particle sizes are 1-5 μm and 5-20 μm respectively.
[0010] Wherein, the complex phase fluorescent ceramic also includes a sintering aid product, and the sintering aid product includes a sintering product of SiO2, CaF2 and Y2O3.
[0011] The composite fluorescent ceramic has a relative density of 98.0%-99.5%.
[0012] The present application also provides a method for preparing a composite fluorescent ceramic, comprising:
[0013] Preparing phosphor particles with at least two particle sizes, coating the surfaces of the phosphor particles with a SiO2 layer and an Al2O3 layer to obtain coated phosphor particles;
[0014] preparing alumina particles and sintering aids;
[0015] The coated phosphor particles, alumina particles and a sintering aid are mixed in proportion to obtain a raw material powder, wherein the weight ratio of the phosphor particles to the alumina particles is 7-9:1-3;
[0016] Molding the raw material powder to obtain a green body;
[0017] The green body is subjected to a first sintering step, wherein the first sintering step satisfies at least one of a sintering temperature of 1400° C. to 1600° C., a sintering time of 0.5 h to 3 h, and a sintering pressure of 30 to 100 MPa;
[0018] The green body sintered in the first step is subjected to a second step of sintering, wherein the second step of sintering satisfies at least one of a sintering temperature of 1400° C. to 1700° C., a sintering time of 10 min to 100 min, and a sintering pressure of 100 to 200 MPa;
[0019] The green body sintered in the second step is annealed to obtain the composite fluorescent ceramic.
[0020] Wherein, the step of coating the surface of the phosphor particles with a SiO2 layer and an Al2O3 layer to obtain coated phosphor particles comprises:
[0021] The phosphor particles, the solvent and the alkoxysilane are mixed, and the alkoxysilane is hydrolyzed to coat the surface of the phosphor particles with a SiO2 layer;
[0022] Centrifugally precipitating the phosphor particles coated with the SiO2 layer and drying them;
[0023] Mixing phosphor particles coated with a SiO2 layer with a solvent and an organic alcohol aluminum, and hydrolyzing the organic alcohol aluminum to coat an Al2O3 layer on the surface of the phosphor particles;
[0024] The phosphor particles are centrifuged and precipitated, and dried to obtain the coated phosphor particles.
[0025] Wherein, the phosphor particles cover multiple layers of the SiO2 layer and the Al2O3 layer.
[0026] Wherein, multiple SiO2 layers and Al2O3 layers are alternately coated on the surface of the phosphor particles, and the mass of the SiO2 and Al2O3 is 0.05%-5% of the mass of the phosphor particles respectively.
[0027] Wherein, the first sintering step is spark plasma sintering; and the second sintering step is hot isostatic pressing sintering.
[0028] The particle sizes of the two phosphor particles with different particle sizes are 10-30 μm and 3-10 μm respectively; the particle size of the aluminum oxide particles is 0.05-1 μm.
[0029] Wherein, the sintering aid includes at least one of tetraethyl orthosilicate, CaF2 and Y2O3, and the mass of the sintering aid is 0.1% to 10% of the mass of the alumina particles.
[0030] The present application also provides a light-emitting device, comprising an excitation light source and the complex phase fluorescent ceramic as described above.
[0031] Beneficial effects of the present application: Different from the prior art, the composite fluorescent ceramic provided by the present application includes fluorescent powder grains and aluminum oxide grains; wherein the fluorescent powder grains include at least two different particle sizes, and the aluminum oxide grains also include at least two different particle sizes. Some of the small-sized aluminum oxide grains are distributed around the fluorescent powder grains and connected to the fluorescent powder grains, so that when the content of the fluorescent powder grains in the composite fluorescent ceramic reaches 70%-90%, the bonding force between the fluorescent powder grains and the aluminum oxide grains can be effectively improved. Moreover, both the fluorescent powder grains and the aluminum oxide grains include at least two particle sizes, so that the aluminum oxide grains can be better bonded to the edges of the fluorescent powder grains, thereby improving the density of the composite fluorescent ceramic, and obtaining a composite fluorescent ceramic with a high fluorescent powder content and high density. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of an embodiment of a complex phase fluorescent ceramic of the present application;
[0033] Figure 2 It is a schematic diagram of the process of the first embodiment of the preparation method provided by the present application;
[0034] Figure 3 It is a flowchart of an embodiment of step S11 of the present application.
[0035] Reference numerals: complex phase fluorescent ceramic 1; fluorescent powder grains 11; aluminum oxide grains 12. DETAILED DESCRIPTION
[0036] The primary purpose of the present application is to increase the content of phosphor grains in the preparation of complex phase fluorescent ceramics to obtain complex phase fluorescent ceramics with high phosphor grain content and high density.
[0037] Based on the above purpose, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the drawings of the embodiment of the present application. It will be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. In the absence of conflict, the following embodiments and the technical features therein may be combined with each other. It should also be noted that, for ease of description, only some but not all structures related to the present application are shown in the drawings. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application.
[0038] See also Figure 1 , Figure 1 1 is a schematic diagram of the structure of an embodiment of a composite fluorescent ceramic of the present application. The composite fluorescent ceramic 1 of the present application comprises fluorescent powder grains 11 and aluminum oxide grains 12.
[0039] The phosphor particles 11 may be formed of yellow phosphor, green phosphor, red phosphor or other phosphor particles, which may be selected according to the needs of the user. In one embodiment, the phosphor particles may be Re:YAG (yttrium aluminum garnet, Y3Al5O 12 ), wherein Re is selected from one of cerium (Ce), lutetium (Lu), europium (Eu), neodymium (Nd), terbium (Tb), ytterbium (Yb) and praseodymium (Pr), and the phosphor grains 11 can absorb the excitation light and emit fluorescence in other bands for use by users or fluorescent devices.
[0040] The phosphor particles 11 include at least two phosphor particles 11 of different particle sizes. Further, the particle sizes of the two phosphor particles 11 are 10-30 μm and 3-10 μm, respectively, preferably 12 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm and 4 μm, 5 μm, 6 μm, 8 μm, 9 μm.
[0041] Among them, at least two phosphor grains 11 with different particle sizes are used to obtain a higher filling rate. The phosphor grains 11 with larger particle sizes are used because: in the composite fluorescent ceramic 1, the phosphor grains 11 will emit light beams of other bands after receiving excitation light, and the intensity of the light beams emitted by the phosphor grains 11 is related to the particle size of the phosphor grains 11. The particle size of the phosphor grains 11 is related to the particle size of the phosphor particles. The phosphor particles, as the raw materials of the phosphor grains 11, can be phosphor particles of two different particle sizes that undergo the same operation steps to form phosphor grains 11 of two different particle sizes, or phosphor particles of the same particle size that undergo different operation steps to form phosphor grains 11 of different particle sizes.
[0042] In the present application, the phosphor particles used as the raw material of the phosphor crystals 11 basically do not participate in the sintering process, so the particle size of the phosphor particles and the phosphor crystals 11 does not change much before and after sintering. The smaller the particle size of the phosphor particles used as the raw material of the phosphor crystals 11, the lower the temperature at which the surface of the phosphor particles enters the liquid phase during the high-temperature sintering of the fluorescent ceramic, and the easier it is to destroy the smooth outer contour of the surface, resulting in a greater decrease in the luminous intensity of the fluorescent ceramic after sintering. Therefore, it is necessary to select phosphor particles with a larger particle size. However, the larger the particle size, the better. The larger the particle size of the phosphor particles, the more difficult it is to sinter, and the more difficult it is to obtain a complex phase fluorescent ceramic 1 with a high density.
[0043] like Figure 1 As shown, in one embodiment of the present application, by selecting at least two particle sizes of phosphor grains 11, the phosphor grains 11 with larger particle sizes, such as the particle size of 10-30μm, can ensure that the smooth outer contour will not be destroyed after sintering, and have good luminescent performance. By combining phosphor grains 11 with smaller particle sizes, such as the particle size of 3-10μm, a better filling rate can be obtained, so that the density of the complex phase fluorescent ceramic 1 finally formed by sintering is higher.
[0044] Furthermore, the particle size of the phosphor crystal grains 11 accounting for 50%-99% of the total number of phosphor crystal grains 11 is within the range of 10-30 μm and 3-10 μm. Preferably, the particle size of the phosphor crystal grains 11 accounting for 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95% of the total number of phosphor crystal grains 11 is within the above range. By making the particle size of as many phosphor crystal grains as possible within the range of 10-30 μm and 3-10 μm, a better filling rate can be obtained, so that the density of the composite fluorescent ceramic 1 finally formed by sintering is higher.
[0045] It should be noted that the particle size of the phosphor crystal grains 11 and the particle size of the alumina crystal grains 12 in the composite fluorescent ceramic 1 of the present application can be determined by Figure 1 The structural diagram shown is respectively Figure 1 The diameters of the maximum circumscribed circles of the outlines of the phosphor crystal grains 11 and the aluminum oxide crystal grains 12 shown in the figure are measured as the particle sizes of the phosphor crystal grains 11 and the aluminum oxide crystal grains 12 , respectively.
[0046] Considering the balance between the luminescent performance and density of the composite fluorescent ceramic 1, the large-sized phosphor crystals 11 can improve the luminescent performance of the fluorescent ceramic, and the small-sized phosphor crystals 11 can improve the filling rate of the fluorescent ceramic during manufacturing. However, when there are too many small-sized phosphor crystals 11, it is not conducive to improving the luminescent performance of the fluorescent ceramic. Therefore, in one embodiment, the number of large-sized phosphor crystals 11 in the phosphor crystals 11 is greater than the number of small-sized phosphor crystals 11, which can effectively improve the luminescent performance of the fluorescent ceramic, and can also improve the filling rate of the fluorescent ceramic, thereby improving the density. Further, in one embodiment, the number of small-sized phosphor crystals 11 accounts for 10-30% of the number of large-sized phosphor crystals 11, preferably 12%, 15%, 20%, 25%, 28%, which can ensure high density while having good luminescent performance.
[0047] The mass of the phosphor grains 11 may be 70%-90% of the mass of the composite fluorescent ceramic 1. Further, the mass fraction of the phosphor grains 11 may be 71%, 72%, 73%, 75%, 76%, 78%, 80%, 81%, 82%, 83%, 85%, 86%, 88%, 89%, 89.5%, etc. In order to improve the luminescent performance of the composite fluorescent ceramic 1, as many phosphor grains 11 as possible are required in the composite fluorescent ceramic 1 to provide luminescent centers. However, the higher the content of the phosphor grains 11, the more difficult it is to densify the composite fluorescent ceramic 1. The present application achieves high density at a high phosphor content. The composite fluorescent ceramic 1 with a high phosphor content of the present application is described in detail below.
[0048] Please continue reading Figure 1 The aluminum oxide grains 12 in the composite fluorescent ceramic 1 also include at least two particle size ranges, that is, at least two aluminum oxide grains 12 with different particle size ranges, wherein some small-size aluminum oxide grains 12 are distributed around the phosphor grains 11 and connected to the phosphor grains 11 .
[0049] By coating the outside of the phosphor particles with multiple layers of SiO2 and Al2O3 layers and then sintering to form phosphor grains 11, the multiple layers of SiO2 and Al2O3 can activate the grain boundaries of the phosphor grains 11 during sintering of the composite fluorescent ceramic 1, and form sufficient liquid phase on the surface of the phosphor grains 11 during the sintering process, which is beneficial to drive the mutual combination of large-particle phosphor grains 11 and small-particle alumina grains 12 (the large particle size and small particle size described here refer to the particle sizes of the phosphor grains 11 and the alumina grains 12 relative to each other, not the absolute size), so that the large-particle phosphor grains 11 and the small-particle alumina grains 12 are more tightly combined, which is beneficial to form a high-density composite fluorescent ceramic 1.
[0050] At the same time, since sufficient liquid phase is provided around the phosphor crystal grains 11, it is beneficial to the material migration of the aluminum oxide crystal grains 12. During the sintering process, the aluminum oxide particles form relatively small-sized aluminum oxide crystal grains 12 around the phosphor crystal grains 11, and some of the aluminum oxide crystal grains 12 in the area far away from the phosphor crystal grains 11 will also fuse to form relatively large-sized aluminum oxide crystal grains 12. Therefore, the sintered composite fluorescent ceramic 1 has at least two types of aluminum oxide crystal grains 12. The aluminum oxide crystal grains 12 with at least two types of particle size ranges are beneficial to the overall filling of the composite fluorescent ceramic 1 and improve the density of the composite fluorescent ceramic 1 formed by sintering.
[0051] In one embodiment, the particle sizes of the two different particle size ranges of the aluminum oxide grains 12 are 1-5 μm and 5-20 μm, respectively. More preferably, the particle sizes are 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 9 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 15.5 μm, 16 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 19.5 μm.
[0052] Further, the particle size of the aluminum oxide grains 12 accounting for 50%-95% of the total number of the aluminum oxide grains 12 is within the range of 1-5μm and 5-20μm. Preferably, the particle size of the aluminum oxide grains 12 accounting for 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 93% of the total number of the aluminum oxide grains 12 is within the above range. By making the particle size of as many phosphor particles as possible within the range of 1-5μm and 5-20μm, a better filling rate can be obtained, so that the density of the composite fluorescent ceramic 1 finally formed by sintering is higher. In addition, the ratio of the number of large-size alumina grains 12 to the number of small-size alumina grains 12 can be 0.1-5, for example, 0.2, 0.4, 0.5, 0.6, 0.8, 0.9, 1.0, 1.2, 1.3, 1.5, 1.6, 1.8, 2, 2.5, 2.8, 3.0, 3.5, 4, 4.2, 4.5, 4.6, 4.8, etc. A better filling rate can be obtained, so that the density of the composite fluorescent ceramic 1 finally formed by sintering is higher.
[0053] Optionally, the composite fluorescent ceramic 1 provided in this embodiment also includes a sintering aid product (not shown). The sintering aid product includes a sintering product of at least one of SiO2 (silicon dioxide), CaF2 (calcium fluoride) and Y2O3 (yttrium oxide). The added sintering aid forms a large amount of liquid phase during the sintering process, which is helpful for the migration of substances and the filling of internal pores, thereby achieving the densification of the fluorescent ceramic. At the same time, it also reduces the sintering temperature inside the fluorescent ceramic, so that the phosphor grains 11 can maintain their original state, and the luminous performance is less affected, and finally a high-phosphor content, high-efficiency, high-density composite fluorescent ceramic 1 is obtained. In addition, the sintering aid product gathers at the grain boundary after sintering, and can serve as a scattering phase of the composite fluorescent ceramic 1, which plays a role in hindering the lateral propagation of light and can reduce the diffusion of light.
[0054] The composite fluorescent ceramic 1 has a relative density of 98.0%-99.5%. Further, the relative density of the phosphor grains 11 can be 98.1%, 98.2%, 98.3%, 98.5%, 98.6%, 98.8%, 98.9%, 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, etc. The present application achieves high density while having large-size phosphor grains 11 and high phosphor grain 11 content.
[0055] In summary, the mass of the phosphor grains 11 in the composite fluorescent ceramic 1 proposed in the embodiment of the present application is as high as 70%-90%, which can provide a large number of luminescent centers for the composite fluorescent ceramic 1, and effectively improve the luminescent performance of the composite fluorescent ceramic 1. And by using phosphor grains 11 and alumina grains 12 of various particle sizes, a higher filling rate can be obtained, so that the composite fluorescent ceramic 1 has a relative density of 98.0%-99.5%. The high density of the composite fluorescent ceramic 1 of the present application can make the composite fluorescent ceramic 1 have good mechanical strength and mechanical processing performance. For example, when the composite fluorescent ceramic 1 is polished, the alumina grains 12 are not easy to fall off, and a good surface roughness can be obtained, which is conducive to subsequent operations such as coating or bonding.
[0056] In order to obtain the above-mentioned complex phase fluorescent ceramic 1, the present application also provides a method for preparing the complex phase fluorescent ceramic 1, such as Figure 2 As shown, Figure 2 1 is a flow chart of the first embodiment of the preparation method provided by the present application. Taking the raw materials of the phosphor crystals 11 of two different particle sizes as phosphor particles of two different particle sizes as an example, the method includes the following steps:
[0057] S11: preparing phosphor particles with at least two particle sizes, and coating the surfaces of the phosphor particles with a silicon dioxide layer and an aluminum oxide layer to obtain coated phosphor particles.
[0058] The surfaces of phosphor particles of at least two particle sizes are coated with a SiO2 layer (silicon dioxide layer) and an Al2O3 layer (aluminum oxide layer), which can activate the grain boundaries of the phosphor grains 11 during the sintering process of the phosphor ceramic. During the sintering, sufficient liquid phase is formed on the surface of the phosphor grains 11, so that the small-size aluminum oxide grains 12 and the phosphor grains 11 are more tightly bonded, thereby improving the bonding force between the phosphor grains 11 and the aluminum oxide grains 12. Among them, the particle sizes of two phosphor particles with different particle sizes (the particle size of the phosphor particles used as raw materials here can be considered as the median particle size D50) are respectively in the range of 10-30μm and 3-10μm, and the SiO2 layer and the Al2O3 layer are alternately coated on the surface of the phosphor particles. That is, in this embodiment, when the SiO2 layer and the Al2O3 layer are coated on the surface of the phosphor particles, a layer of SiO2 layer can be coated on the surface of the phosphor particles first, and then the phosphor particles coated with the SiO2 layer are placed in the reagent and then coated with a layer of Al2O3 layer. The surface of the phosphor particles can be coated with SiO2 layers and Al2O3 layers repeatedly to coat the surface of the phosphor particles with enough SiO2 and Al2O3, while avoiding the problem of too large a thickness of the SiO2 layer or the Al2O3 layer coated at one time, resulting in insufficient surface bonding between the SiO2 layer and the Al2O3 layer and the phosphor particles. It is understandable that in other embodiments, the surface of the phosphor particles may be coated with an Al2O3 layer first and then with a SiO2 layer.
[0059] Furthermore, in one embodiment of the present application, the surface of the phosphor particles may be covered with 3-10 layers of SiO2 layers and Al2O3 layers, wherein the number and thickness of the SiO2 layers and Al2O3 layers may be different.
[0060] Among them, the mass of the SiO2 layer and the Al2O3 layer can be 0.05-5% of the mass of the phosphor particles, preferably 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%. Since the SiO2 layer and the Al2O3 layer enhance the bonding force between the phosphor crystal grains 11 and the alumina crystal grains 12 during the sintering process, the mass of the SiO2 layer and the Al2O3 layer should not be too small. And since if the thickness of the coated SiO2 layer and the Al2O3 layer is too thick, too much liquid phase may be formed during the sintering process, which is not conducive to improving the bonding force between the phosphor crystal grains 11 and the alumina crystal grains 12, the thickness of the SiO2 layer and the Al2O3 layer should not be too large. In this embodiment, the mass of the SiO2 layer and the Al2O3 layer is 0.05-5% of the mass of the phosphor particles, which can effectively improve the bonding force between the phosphor crystal grains 11 and the alumina crystal grains 12.
[0061] S12: preparing alumina particles and sintering aids.
[0062] During the sintering process, the alumina particles undergo a melting-crystallization process to form alumina grains 12 of at least two particle size ranges, which are combined around the phosphor grains 11 to combine multiple phosphor grains 11 to form a high-density fluorescent ceramic. In one embodiment of the present application, the particle size of the prepared alumina particles (the particle size of the alumina particles used as the raw material here can be considered as the median particle size D50) is 0.05-1 μm.
[0063] The type of sintering aid is not particularly limited in the present application. In one embodiment of the present application, the sintering aid includes at least one of tetraethyl orthosilicate, CaF2 and Y2O3, which is used to reduce the sintering temperature of the fluorescent ceramic during the sintering process to avoid the high temperature causing the smooth outer contour of the fluorescent powder grains 11 to be destroyed. At the same time, tetraethyl orthosilicate will produce liquid SiO2 in the sintering process that is free around the fluorescent powder grains 11, facilitating the material migration of the aluminum oxide grains 12 around the fluorescent powder grains 11, promoting the mutual bonding of the aluminum oxide grains 12, and the close bonding between the fluorescent powder grains 11 and the aluminum oxide grains 12.
[0064] In one embodiment of the present application, the total mass of the sintering aid accounts for 0.1-10% of the mass of the alumina particles, preferably 0.5%, 1%, 2%, 2.5%, 3%, 5%, 6%, 7%, 7.5%, 8%, 9%. During the sintering process, the sintering aid can not only promote the mutual bonding of the alumina particles to form alumina grains 12 with at least two particle sizes, but also improve the bonding force between the alumina grains 12 and the phosphor grains 11.
[0065] It is worth noting that the quality of the sintering aid is not the more the better. When too much sintering aid is added during sintering, the sintering aid may form too much liquid phase, which is not conducive to improving the bonding force between the phosphor grains 11 and the alumina grains 12, thereby reducing the mechanical density of the fluorescent ceramic. Therefore, in this embodiment, the mass of the sintering aid accounts for 0.1-10% of the mass of the alumina particles.
[0066] S13: Mix the coated phosphor particles, alumina particles and a sintering aid in proportion to obtain a raw material powder.
[0067] In one embodiment, the alumina particles and the sintering aid may be mixed in advance, and then mixed with the coated phosphor particles obtained in step S11; in another embodiment, the coated phosphor particles obtained in step S11 may be fully mixed with the alumina particles and the sintering aid. Further, the coated phosphor particles, the alumina particles and the sintering aid may be fully mixed by ball milling to obtain a mixed slurry, and then the mixed slurry may be dried at 60-80° C. for 10-20 hours, and then crushed and sieved to obtain a raw material powder.
[0068] The mixing ratio of the phosphor particles and the alumina particles can be varied, and the content of the phosphor crystals 11 in the composite fluorescent ceramic 1 provided by the present application reaches 70%-90%. In this embodiment, the weight ratio of the phosphor particles to the alumina particles can be 7-9:1-3.
[0069] S14: forming the raw material powder into a green body.
[0070] In one embodiment, the raw material powder obtained in step S13 may be filled into a graphite mold and pre-pressed to obtain a green body.
[0071] S15: performing the first step of sintering on the green body.
[0072] In one embodiment of the present application, the first sintering step is spark plasma sintering. The graphite mold containing the green body is placed in a spark plasma sintering furnace for spark plasma sintering. This process can be carried out in a vacuum or argon environment, and at least one of the sintering temperature is 1400-1600°C, the sintering pressure is 30-100MPa, and the sintering time is 0.5-3h.
[0073] S16: performing a second sintering on the green body sintered in the first step.
[0074] In one embodiment of the present application, the green body obtained in the first step of sintering in step S15 is placed in a hot isostatic pressing furnace for hot isostatic pressing sintering. This process can be carried out in a nitrogen or argon environment, and at least one of the sintering temperature is 1400-1700°C, the sintering pressure is 100-200MPa, and the sintering time is 10-100min.
[0075] During the sintering process of step S15 and step S16, the SiO2 layer and the Al2O3 layer coated on the surface of the phosphor particles can activate the grain boundaries of the phosphor grains 11. At the same time, sufficient liquid phase will be formed during the sintering process, so that the aluminum oxide grains 12 can have better fluidity in the gaps between multiple phosphor grains 11. Under high pressure conditions, the pores inside the fluorescent ceramic are gradually filled, and the phosphor grains 11 and the aluminum oxide grains 12 are more tightly bonded to each other, thereby effectively improving the density of the composite fluorescent ceramic 1.
[0076] The traditional preparation method is mainly atmospheric sintering or vacuum sintering. The driving force for densification of this method mainly comes from the crystallization-growth process of alumina particles in fluorescent ceramics and the liquid phase flow of sintering aids. When the content of large-size phosphor particles is high and the content of alumina grains is low, the sintering power is not enough to densify the fluorescent ceramics with this structure, that is, the material exchange and recrystallization process of alumina grains cannot promote the displacement and mutual combination of phosphor particles. If the sintering temperature is further increased (such as to 1800℃) to increase the sintering driving force, not only will it still fail to be sintered, but it will also easily cause serious deformation of the phosphor particles in the fluorescent ceramics (destroying the smooth surface of the phosphor particles), causing the luminescence performance of the phosphor particles to drop sharply.
[0077] In the sintering process of the fluorescent ceramic with high content and large particle size of fluorescent powder crystal grains 11, the present application adopts a two-step sintering method of coating fluorescent powder particles and using spark plasma sintering and hot isostatic pressing sintering to introduce a sufficiently large external pressure to promote the mutual combination of large particle size fluorescent powder crystal grains 11 and small particle size aluminum oxide crystal grains 12. In addition, by coating the surface of the fluorescent powder particles with SiO2 layer and Al2O3 layer and adding sintering aid to produce liquid SiO2, the sintering temperature inside the fluorescent ceramic is low, and sintering densification is achieved at a low sintering temperature. The fluorescent powder particles can maintain their original state well, and the luminous performance is not greatly affected, and finally a high-density and high-light-efficiency fluorescent ceramic is obtained.
[0078] S17: annealing the green body sintered in the second step to obtain a composite fluorescent ceramic 1.
[0079] In one embodiment of the present application, the second sintered green body obtained in step S16 can be annealed for 1-20 hours in air or a reducing gas (such as hydrogen, carbon monoxide, methane, etc.) at a temperature of 1100-1400°C to remove carbon ions and other impurity ions that have infiltrated into the fluorescent ceramic during the sintering process, thereby improving the luminous efficiency of the fluorescent ceramic.
[0080] See also Figure 3 , Figure 3 This is a flow chart of an embodiment of step S11 of the present application. The specific steps of coating the surface of the phosphor particles with SiO2 layers and Al2O3 layers to obtain the coated phosphor particles include:
[0081] S111: mixing phosphor particles, a solvent and alkoxysilane, and hydrolyzing the alkoxysilane to coat the surface of the phosphor particles with a silicon dioxide layer.
[0082] In this step, the solvent may include hydrochloric acid solution, ammonia solution, etc., and the phosphor particles are mixed with the solvent and alkoxysilane. The alkoxysilane is hydrolyzed under the catalysis of the solvent. When the hydrolysis is completed, the surface of the phosphor particles will be coated with a layer of SiO2. Alkoxysilane includes but is not limited to ethyl orthosilicate, etc.
[0083] S112: centrifugally precipitating the phosphor particles coated with the silicon dioxide layer, and drying the particles.
[0084] Since step S111 is carried out in a solvent, the obtained phosphor particles coated with the SiO2 layer are in a liquid, and there are other substances generated by the hydrolysis reaction in the liquid, which need to be removed. Therefore, the liquid after the reaction is centrifuged to obtain phosphor particles coated with the SiO2 layer in a wet state, and the phosphor particles are dried to obtain phosphor particles coated with the SiO2 layer in a dry state.
[0085] S113: mixing phosphor particles coated with a silicon dioxide layer with a solvent and organic alcohol aluminum to coat an aluminum oxide layer on the surface of the phosphor particles.
[0086] In this embodiment, it is necessary to coat the phosphor particles with a SiO2 layer and an Al2O3 layer, that is, in this step, the phosphor particles coated with the SiO2 layer obtained in step S112 can be mixed with a solvent and an organic alcohol aluminum, wherein the solvent can include a hydrochloric acid solution, an ammonia solution, etc. The solvent can catalyze the hydrolysis of the organic alcohol aluminum. After the hydrolysis is completed, the surface of the phosphor particles will be covered with an Al2O3 layer, thereby obtaining phosphor particles coated with a SiO2 layer and an Al2O3 layer. The organic alcohol aluminum includes but is not limited to aluminum isopropoxide, etc.
[0087] S114: centrifugally precipitating and drying the phosphor particles to obtain coated phosphor particles.
[0088] The phosphor particles coated with the SiO2 layer and the Al2O3 layer are centrifugally precipitated from the liquid after the reaction in step S113, and dried to obtain the coated phosphor particles in a dry state.
[0089] It should be noted that after the organic alcohol aluminum is hydrolyzed in step S113, the Al2O3 layer may not be directly coated on the surface of the phosphor particles, but a precursor layer of the Al2O3 layer is first formed, such as AlOOH (aluminum hydroxide), Al(OH)3 (aluminum hydroxide), etc., which is also referred to as Al2O3 layer in this application.
[0090] In one embodiment of the present application, the surface of the phosphor particles can be alternately coated with different numbers of SiO2 layers and Al2O3 layers. Based on this, the user can repeat steps S111 to S114 on the phosphor particles to obtain coated phosphor particles coated with multiple SiO2 layers and Al2O3 layers.
[0091] The present application also provides a light-emitting device (not shown), including an excitation light source and a complex fluorescent ceramic 1. The complex fluorescent ceramic 1 can be arranged around the excitation light source. When receiving the excitation light generated by the excitation light source, the phosphor grains 11 in the complex fluorescent ceramic 1 absorb the excitation light and generate multi-angle fluorescence with different wavelengths from the excitation light for use by users or fluorescent devices. The light-emitting devices of the present application include but are not limited to LED light sources, LD light sources, lighting devices, projection devices, etc.
[0092] For the composite fluorescent ceramics 1 with different contents of phosphor particles, the preparation methods of the present application are different. For example, the proportions of phosphor particles, alumina particles and sintering aids in the raw material powder will be different, the number, thickness and stacking order of SiO2 layers and Al2O3 layers covering the phosphor particles will be different, the contents of ethyl orthosilicate, CaF2 and Y2O3 in the sintering aid will be different, the sintering temperature, sintering time and sintering pressure required for spark plasma sintering and hot isostatic pressing will be different, the temperature and time of annealing treatment will also be different, please continue to refer to Figure 2 and Figure 3 , which will be described below with reference to specific embodiments.
[0093] Example 1
[0094] The preparation method of the composite fluorescent ceramic comprises the following steps:
[0095] Two types of YAG yellow phosphor particles with particle sizes of 10 μm and 3 μm were prepared, and the number of the phosphor particles with the small particle size accounted for 10% of the number of the phosphor particles with the large particle size.
[0096] First, the phosphor particles are mixed with deionized water and placed in a stirrer to keep the phosphor particles in a suspended and flowing state. A 1% mass fraction of tetraethyl orthosilicate solution is added to the stirrer, and then a hydrochloric acid solution is slowly dripped in to promote the hydrolysis of tetraethyl orthosilicate. After the hydrolysis of tetraethyl orthosilicate, a layer of SiO2 will be covered on the surface of the phosphor particles. The coated phosphor particles are then centrifuged and dried to obtain phosphor particles covered with a SiO2 layer.
[0097] The phosphor particles covered with the SiO2 layer are then mixed with deionized water and placed in a stirrer for stirring. A 1% by mass aluminum isopropoxide solution is added to the stirrer, and then a hydrochloric acid solution is slowly dripped into the stirrer to promote the hydrolysis of the aluminum isopropoxide. After the hydrolysis of the aluminum isopropoxide, a layer of Al2O3 layer will be covered on the surface of the phosphor particles. The coated phosphor particles are then centrifuged and dried to obtain coated phosphor particles.
[0098] The above steps are repeated five times on the phosphor particles to obtain coated phosphor particles having five SiO2 layers and five Al2O3 layers.
[0099] Prepare alumina particles with a particle size of 1 μm and sintering aids (TEOS, nano-CaF2 particles and nano-Y2O3 particles), mix the coated phosphor particles, alumina particles, sintering aids and anhydrous ethanol, and ball mill for 12 hours. Dry the mixed raw materials at 80°C for 10 hours, then crush and sieve to obtain raw material powder. Among them, the mass of ethyl orthosilicate in the sintering aid accounts for 5% of the mass of alumina particles, the mass of nano-CaF2 particles accounts for 0.5% of the mass of alumina particles, and the mass of nano-Y2O3 particles accounts for 0.8% of the mass of alumina particles. The mass ratio between phosphor particles and alumina particles is 7:3.
[0100] The raw material powder is heat treated at 600° C. for 2 hours, the heat treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.
[0101] The obtained green body is placed in a spark plasma sintering furnace for the first step of sintering in a vacuum environment with a sintering temperature of 1400° C., a sintering pressure of 30 MPa and a sintering time of 0.5 h.
[0102] The green body sintered in the first step was placed in a hot isostatic pressing furnace for the second step of sintering in a nitrogen environment at a sintering temperature of 1400° C., a sintering pressure of 100 MPa, and a sintering time of 10 min.
[0103] The green body sintered in the second step is annealed at 1200° C. for 8 hours in a reducing gas environment to remove carbon ions that have infiltrated into the fluorescent ceramic during the sintering process.
[0104] The fluorescent ceramics can be further cut, ground and polished to obtain complex-phase fluorescent ceramics with high fluorescent powder content.
[0105] Example 2
[0106] The preparation method of the composite fluorescent ceramic comprises the following steps:
[0107] Two types of YAG yellow phosphor particles with particle sizes of 30 μm and 10 μm were prepared, and the number of the phosphor particles with the small particle size accounted for 30% of the number of the phosphor particles with the large particle size.
[0108] First, the phosphor particles are mixed with deionized water and placed in a stirrer to keep the phosphor particles in a suspended and flowing state. A 1% mass fraction of tetraethyl orthosilicate solution is added to the stirrer, and then a hydrochloric acid solution is slowly dripped in to promote the hydrolysis of tetraethyl orthosilicate. After the hydrolysis of tetraethyl orthosilicate, a layer of SiO2 will be covered on the surface of the phosphor particles. The coated phosphor particles are then centrifuged and dried to obtain phosphor particles covered with a SiO2 layer.
[0109] The phosphor particles covered with the SiO2 layer are then mixed with deionized water and placed in a stirrer for stirring. A 1% by mass aluminum isopropoxide solution is added to the stirrer, and then a hydrochloric acid solution is slowly dripped into the stirrer to promote the hydrolysis of the aluminum isopropoxide. After the hydrolysis of the aluminum isopropoxide, a layer of Al2O3 layer will be covered on the surface of the phosphor particles. The coated phosphor particles are then centrifuged and dried to obtain coated phosphor particles.
[0110] The above steps are repeated ten times on the phosphor particles to obtain coated phosphor particles having ten SiO2 layers and ten Al2O3 layers.
[0111] Prepare alumina particles with a particle size of 0.05 μm and sintering aids (TEOS, nano-CaF2 particles and nano-Y2O3 particles), mix the coated phosphor particles, alumina particles, sintering aids and anhydrous ethanol, and ball mill for 12 hours. The mixed raw materials are dried at 80°C for 10 hours, then crushed and sieved to obtain raw material powder. Among them, the mass of ethyl orthosilicate in the sintering aid accounts for 3% of the mass of alumina particles, the mass of nano-CaF2 particles accounts for 0.8% of the mass of alumina particles, and the mass of nano-Y2O3 particles accounts for 0.5% of the mass of alumina particles. The mass ratio between phosphor particles and alumina particles is 9:1.
[0112] The raw material powder is heat treated at 700° C. for 3 hours, the heat-treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.
[0113] The obtained green body is placed in a spark plasma sintering furnace for the first step of sintering in a vacuum environment with a sintering temperature of 1600° C., a sintering pressure of 100 MPa and a sintering time of 3 h.
[0114] The green body sintered in the first step was placed in a hot isostatic pressing furnace for the second step of sintering in a nitrogen environment at a sintering temperature of 1700° C., a sintering pressure of 200 MPa, and a sintering time of 100 min.
[0115] The green body sintered in the second step is annealed at 1200° C. for 8 hours in a reducing gas environment to remove carbon ions that have infiltrated into the fluorescent ceramic during the sintering process.
[0116] The fluorescent ceramics can be further cut, ground and polished to obtain complex-phase fluorescent ceramics with high fluorescent powder content.
[0117] It is noted again that the above is only an implementation method of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A complex phase fluorescent ceramic, characterized in that: The complex fluorescent ceramic includes fluorescent powder grains and aluminum oxide grains; wherein the fluorescent powder grains include at least two kinds of fluorescent powder grains with different particle sizes; the aluminum oxide grains include at least two kinds of aluminum oxide grains with different particle sizes, wherein at least some of the aluminum oxide grains with small particle sizes are distributed around the fluorescent powder grains and connected to the fluorescent powder grains; the mass of the fluorescent powder grains is 70%-90% of the mass of the complex fluorescent ceramic.
2. The complex fluorescent ceramic according to claim 1, characterized in that: The particle sizes of the two phosphor crystal particles with different particle sizes are respectively in the range of 10-30 μm and 3-10 μm.
3. The complex fluorescent ceramic according to claim 1 or 2, characterized in that: The number of the phosphor crystal particles with small particle size accounts for 10-30% of the number of the phosphor crystal particles with large particle size.
4. The complex fluorescent ceramic according to claim 1, characterized in that: The particle size ranges of the two aluminum oxide grains with different particle sizes are 1-5 μm and 5-20 μm respectively.
5. The complex fluorescent ceramic according to claim 1, characterized in that: The complex phase fluorescent ceramic further includes a sintering aid product, and the sintering aid product includes a sintering product of SiO2, CaF2 and Y2O3.
6. The complex fluorescent ceramic according to claim 1, characterized in that: The complex phase fluorescent ceramic has a relative density of 98.0%-99.5%.
7. A method for preparing a composite fluorescent ceramic, characterized in that: include: Preparing phosphor particles with at least two particle sizes, coating the surfaces of the phosphor particles with a SiO2 layer and an Al2O3 layer to obtain coated phosphor particles; preparing alumina particles and sintering aids; The coated phosphor particles, alumina particles and a sintering aid are mixed in proportion to obtain a raw material powder, wherein the weight ratio of the phosphor particles to the alumina particles is 7-9:1-3; Molding the raw material powder to obtain a green body; The green body is subjected to a first sintering step, wherein the first sintering step satisfies at least one of a sintering temperature of 1400° C. to 1600° C., a sintering time of 0.5 h to 3 h, and a sintering pressure of 30 to 100 MPa; The green body sintered in the first step is subjected to a second step of sintering, wherein the second step of sintering satisfies at least one of a sintering temperature of 1400° C. to 1700° C., a sintering time of 10 min to 100 min, and a sintering pressure of 100 to 200 MPa; The green body sintered in the second step is annealed to obtain the composite fluorescent ceramic.
8. The preparation method according to claim 7, characterized in that: The step of coating the surface of the phosphor particles with a SiO2 layer and an Al2O3 layer to obtain coated phosphor particles comprises: The phosphor particles, the solvent and the alkoxysilane are mixed, and the alkoxysilane is hydrolyzed to coat the surface of the phosphor particles with a SiO2 layer; Centrifugally precipitating the phosphor particles coated with the SiO2 layer and drying them; Mixing phosphor particles coated with a SiO2 layer with a solvent and an organic alcohol aluminum, and hydrolyzing the organic alcohol aluminum to coat an Al2O3 layer on the surface of the phosphor particles; The phosphor particles are centrifuged and precipitated, and dried to obtain the coated phosphor particles.
9. The preparation method according to claim 7 or 8, characterized in that: Multiple SiO2 layers and Al2O3 layers are alternately coated on the surface of the phosphor particles, and the mass of the SiO2 and Al2O3 is 0.05%-5% of the mass of the phosphor particles respectively.
10. The preparation method according to claim 7, characterized in that: The first sintering step is spark plasma sintering; the second sintering step is hot isostatic pressing sintering.
11. The preparation method according to claim 7, characterized in that: The particle sizes of the two phosphor particles with different particle sizes are 10-30 μm and 3-10 μm respectively; the particle size of the aluminum oxide particles is 0.05-1 μm.
12. The preparation method according to claim 7, characterized in that: The sintering aid comprises at least one of tetraethyl orthosilicate, CaF2 and Y2O3, and the mass of the sintering aid is 0.1% to 10% of the mass of the alumina particles.
13. A light emitting device, characterized in that: It comprises an excitation light source and the complex fluorescent ceramic according to any one of claims 1 to 6.